The effect of sustainability on new product development in manufacturing-internal and external practices - Zahra Ahmadi-Gh; Alejandro Bello-Pintado (Administrative Sciences, 2021)
The purpose of this paper is to analyse the link between the adoption of sustainability practices and new product development (NPD) in manufacturing companies. From a triple bottom line (TBL) perspective and considering different theoretical approaches, this study hypothesises on the effect of both internal and external sustainability practices, distinguishing between collaborative and controlling initiatives, on the success of new products. Using a unique database of 281 companies across three industries taken from the fourth round of the High-Performance Manufacturing project, the findings shows that both monitoring and collaborative actions with suppliers demonstrate positive impacts on NPD success. Internal sustainability practices do not have a direct effect on NPD success but are determinant in supporting external sustainability practices.
Keywords: 350; collaboration; external sustainability practices; internal sustainability practices; monitoring; new product development success